Analisis Presepsi Guru Tentang Pembelajaran Ilmu Pengetahuan Sosial Sekolah Dasar Berbasis Lingkungan - Irene Widya Siswanti; Sudarti Sudarti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Environmental-based elementary school social science learning is a very important lesson in building a sense of concern for students about the surrounding environment both at school and in the community. However, teacher perceptions are needed in understanding environmental-based learning in order to apply it to classroom learning. Therefore, this study aims to analyze the teacher's perception of environmental- based Social Science learning. This research was conducted through surveys and giving questionnaires to school teachers, the sample of this study was 25 respondents from SDN Watugolong 02 teachers. The data of this study were analyzed using data interpretation analysis. The results of this study indicate that teachers' perceptions are positive about environmental-based Social Science-based learning with a percentage of 60% of 25 respondents and teachers give reasons that this learning will have a positive impact on elementary school students. In conclusion, the teacher's perception of environmental- based social studies learning is very positive. The positive thing in question is to build the character of students to foster a sense of care for the environment such as throwing garbage in its place.